Tetraspanins as regulators of the tumour microenvironment: implications for metastasis and therapeutic strategies - Detchokul, S (Br J Pharmacol, 2014)
One of the hallmarks of cancer is the ability to activate invasion and metastasis. Cancer morbidity and mortality are largely related to the spread of the primary, localized tumour to adjacent and distant sites. Appropriate management and treatment decisions based on predicting metastatic disease at the time of diagnosis is thus crucial, which supports better understanding of the metastatic process. There are components of metastasis that are common to all primary tumours: dissociation from the primary tumour mass, reorganization/remodelling of extracellular matrix, cell migration, recognition and movement through endothelial cells and the vascular circulation and lodgement and proliferation within ectopic stroma. One of the key and initial events is the increased ability of cancer cells to move, escaping the regulation of normal physiological control. The cellular cytoskeleton plays an important role in cancer cell motility and active cytoskeletal rearrangement can result in metastatic disease. This active change in cytoskeletal dynamics results in manipulation of plasma membrane and cellular balance between cellular adhesion and motility which in turn determines cancer cell movement. Members of the tetraspanin family of proteins play important roles in regulation of cancer cell migration and cancer-endothelial cell interactions, which are critical for cancer invasion and metastasis. Their involvements in active cytoskeletal dynamics, cancer metastasis and potential clinical application will be discussed in this review. In particular, the tetraspanin member, CD151, is highlighted for its major role in cancer invasion and metastasis. LINKED ARTICLES: This article is part of a themed section on Cytoskeleton, Extracellular Matrix, Cell Migration, Wound Healing and Related Topics. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue-24